Fabrication and evaluation of electrohydrodynamic jet 3D printed polycaprolactone/chitosan cell carriers using human embryonic stem cell-derived fibroblasts. (August 2016) - Wu, Yang; Sriram, Gopu; Fawzy, Amr S; Fuh, Jerry YH; Rosa, Vinicius; Cao, Tong; Wong, Yoke San
Biological function of adherent cells depends on the cell–cell and cell–matrix interactions in three-dimensional space. To understand the behavior of cells in 3D environment and their interactions with neighboring cells and matrix requires 3D culture systems. Here, we present a novel 3D cell carrier scaffold that provides an environment for routine 3D cell growth in vitro . We have developed thin, mechanically stable electrohydrodynamic jet (E-jet) 3D printed polycaprolactone and polycaprolactone/Chitosan macroporous scaffolds with precise fiber orientation for basic 3D cell culture application. We have evaluated the application of this technology by growing human embryonic stem cell-derived fibroblasts within these 3D scaffolds. Assessment of cell viability and proliferation of cells seeded on polycaprolactone and polycaprolactone/Chitosan 3D-scaffolds show that the human embryonic stem cell-derived fibroblasts could adhere and proliferate on the scaffolds over time. Further, using confocal microscopy we demonstrate the ability to use fluorescence-labelled cells that could be microscopically monitored in real-time. Hence, these 3D printed polycaprolactone and polycaprolactone/Chitosan scaffolds could be used as a cell carrier for in vitro 3D cell culture-, bioreactor- and tissue engineering-related applications in the future.